Rancang Bangun Sistem Informasi Digital untuk Pendataan Aset Daerah Kabupaten Kolaka - Hardiyanti Rukmana; Adawiyah, Rabiah (Fakultas Teknologi Informasi, 2025)
Regional asset data management is essential for government financial management to guarantee openness, accountability, and efficiency in the use of public assets. The Regional Financial and Asset Agency (BKAD) of Kolaka Regency formerly utilized manual procedures with Microsoft Excel, which presented numerous restrictions, including the potential for recording errors, data duplication, and delays in report generation. This project seeks to create a Digital Information System for Regional Asset Data Management in Kolaka Regency utilizing a web-based platform to tackle these difficulties. The system development adheres to the Waterfall process, which includes requirement analysis, design, implementation, and testing phases. The technology stack comprises PHP as the programming language and MySQL as the database. The system underwent Black Box Testing, which confirmed its efficacy in enhancing data accuracy, accelerating information retrieval, and facilitating automatic report preparation based on asset acquisition years. The evaluation results demonstrate that the created system improves asset management efficiency and facilitates superior decision-making processes.